Robotic-assisted surgical systems in treatment of breast cancer: applications and prospects - ZHAO Xin, GAO Peng, CHEN Jie (Waike lilun yu shijian)
In recent years, minimally invasive surgical techniques represented by endoscopic techniques and robotic surgical systems have become a new trend in the development of surgical treatment. With the advantages of precision, minimally invasive and aesthetics, robotic surgery has been more and more widely used in the field of breast surgery. By analysing literature, this paper reviewed the application of robotic surgery in breast cancer treatment in recent years, including the development of the technology, feasibility and safety of the surgery, etc., so as to provide a theoretical basis for the application of robotic surgical systems in breast cancer treatment.